Optimising lithium-ion cell design for plug-in hybrid and battery electric vehicles. (April 2019) - Campbell, Ian D.; Gopalakrishnan, Krishnakumar; Marinescu, Monica; Torchio, Marcello; Offer, Gregory J.; Raimondo, Davide
Graphical abstract: Highlights: Enhanced fast charging and all-electric-range are focal points for xEV researchers. Model-based engineering can supplant empirical or iterative cell design approaches. A framework to optimise layer configurations in automotive pouch cells is presented. Application of methodology to common module pack design is studied for a BEV and PHEV. The open-source Battery Optimal Layer Design (BOLD) toolbox accompanies this study. Abstract: Increased driving range and enhanced fast charging capabilities are two immediate goals of transport electrification. However, these are of competing nature, leading to increased energy and power demand respectively from the on-board battery pack. By fine-tuning the number of layers versus active electrode material of a lithium ion pouch cell, tailored designs targeting either of these goals can be obtained. Achieving this trade-off through iterative empirical testing of layer choices is expensive and often produces sub-optimal designs. This paper presents a model-based methodology for determining the optimal number of layers, maximising usable energy whilst satisfying specific acceleration and fast charging targets. The proposed methodology accounts for the critical need to avoid lithium plating during fast charging and searches for the optimal layer configuration considering a range of thermal conditions. A numerical implementation of a cell model using a hybrid finite volume-spectral scheme is presented, wherein the model equations are suitably reformulated to directly accept power inputs, facilitating rapid and accurate searching of the layer design space. Electrode materials exhibiting high solid phase diffusion rates are highlighted as being equally as important for extended range as the development of new materials with higher inherent capacity. The proposed methodology is demonstrated for the common module design of a battery pack in a plug-in hybrid vehicle, thereby illustrating how the cost of derivative vehicle models can be reduced. To facilitate model based layer optimisation, the open-source toolbox, BOLD (Battery Optimal Layer Design) is provided.